Phenotype-Independent Isolation of Interspecies Saccharomyces Hybrids by Dual-Dye Fluorescent Staining and Fluorescence-Activated Cell Sorting - Gorter de Vries, Arthur R.; Koster, Charlotte C.; Weening, Susan M.; Luttik, Marijke A. H.; Kuijpers, Niels G. A.; Geertman, Jan-Maarten A.; Pronk, Jack T.; Daran, Jean-Marc G. (Frontiers in Microbiology, 2019)
Interspecies hybrids of Saccharomyces species are found in a variety of industrial environments and often outperform their parental strains in industrial fermentation processes. Interspecies hybridisation is therefore increasingly considered as an approach for improvement and diversification of yeast strains for industrial application. However, current hybridisation methods are limited by their reliance on pre-existing or introduced selectable phenotypes. This study presents a high-throughput phenotype-independent method for isolation of interspecies Saccharomyces hybrids based on dual dye-staining and subsequent mating of two strains, followed by isolation of double-stained hybrid cells from a mating population by fluorescence-activated cell sorting (FACS). Pilot experiments on intra-species mating of heterothallic haploid S. cerevisiae strains showed that 80 % of sorted double-stained cells were hybrids. The protocol was further optimized by mating an S. cerevisiae haploid with homothallic S. eubayanus spores with complementary selectable phenotypes. In crosses without selectable phenotype, using S. cerevisiae and S. eubayanus haploids derived from laboratory as well as industrial strains, 10 to 15 % of double-stained cells isolated by FACS were hybrids. When applied to rare mating, sorting of double-stained cells consistently resulted in about 600-fold enrichment of hybrid cells. Mating of dual-stained cells and FACS-based selection allows efficient enrichment of interspecies Saccharomyces hybrids within a matter of days and without requiring selectable hybrid phenotypes, both for homothallic and heterothallic Saccharomyces species. This strategy should accelerate generation of laboratory-made hybrids, facilitate research into hybrid heterosis and offer new opportunities for non-GMO industrial strain improvement and diversification.